(untitled) (Prilozi za orijentalnu filologiju, 2017)
The author describes the usage of the ismu- fā'il in the contemporary Arabic language. Using examples, he shows how this form, in its de facto usage, comes across in the Serbo-Croatian language as noun, adjective, verb, adverb, preposition and ordinal numeral, depending on the context in which it is employed. Hence the active participle in Serbo-Croatian which is commonly used as a term for the ismu-l-fā'il, altohough it does not fully correspond to it, for the usage of the active participle in the Serbo-Croatian language is very limited compared to the usage of the ismu-l fā'il. The nominal usage is the most frequent usage of the ismu-l fā'il. By means of this form there can be formed various no uns which are derived from almost all classes of verbs still usable in Arabic. Also interesting is the usage of the ismu-l- fā'il in its verbal and adjectival meanings.